Economic Downturns, Urban Growth and Suburban Fertility in a Mediterranean Context - Samaneh Sadat Nickayin; Francesco Chelli; Rosario Turco; Bogdana Nosova; Chara Vavoura; Luca Salvati (Economies, 2022)
Despite the wealth of micro–macro data on short-term demographic dynamics, the impact of metropolitan growth and economic downturns on local fertility is still under-investigated in advanced economies. Recent studies in low-fertility contexts have assumed suburban birth rates as being systematically higher than urban and rural rates. This assumption (hereafter, known as the ‘suburban fertility hypothesis’) was grounded on stylized facts and spatial regularities that imply a significant role of both macro (contextual) and micro (behavioral) factors positively influencing fertility in suburban locations. To verify such a hypothesis from a macro (contextual) perspective, the present study compares the general fertility rate of urban, suburban, and rural settlements of the Athens’ metropolitan region (Greece) at various observation years between 1860 and 2020. Long-term Athens’ growth represented a sort of ‘quasi-experiment’ for Mediterranean Europe, linking sequential urban stages and distinctive waves of economic expansion and recession. Using multivariate exploratory analysis and global/local econometric models, a dominant ‘rural’ fertility regime was recorded for 1860 and 1884. A characteristic ‘urban’ fertility regime was, instead, found over a relatively long, intermediate period between 1956 and 1990. Higher fertility in suburban settlements (10 km away from downtown Athens, on average) was, finally, observed since 2000. Considering a sufficiently long-time interval, the existence of multiple fertility regimes along the distance gradient has demonstrated how fertility dynamics are intrinsically bonded with metropolitan growth, economic downturns, and social transformations in Mediterranean Europe.